DEVELOPMENT OF TRANSITION METAL SULFIDE NANOPARTICLES FOR ENERGY STORAGE APPLICATION - Alief Irham, Muhammad
Energy storage is one of the breakthroughs in this decade, becoming one of the answers to stop global warming through electric vehicle (EV) utilization. Among many energy storage devices, Supercapacitors have risen as an energy storage device as they could provide high-energy density in high-power density. Through EDLC and Pseudocapacitors, supercapacitor allows many technologies to use renewable energy as their sources. However, supercapacitor performance is dependent on their electrode. Nanoparticle, a nanosized particle with a high surface-area-to-volume ratio, offers a vast potency to produce a high-energy supercapacitor. Several breakthrough materials such as Transition Metal Sulfide (TMS), MXene, Graphene, and Metal Organic Framework has been proven as high-performance supercapacitor materials. Increasing their performance through conductive agent cooperation, surface functionalization, and optimizing their surface is an intriguing solution to their problem. Despite many efforts to increase the supercapacitor performance, the current energy density status still needs to be enhanced. However, reducing the TMS size to nanometer scale has been challenging issues and has not been explored yet. Also, further exploration, either from experimental or computational work, is still needed. This study combined the experimental and simulation to answer the need for a higher energy density supercapacitor. Several simulations based on first-principles study was utilized to search either new material or a new mechanism to enhance supercapacitor, i.e., quantum capacitance. The first-principles calculation gives a guideline for synthesizing high-performance supercapacitors. Dopant role were rigorously discussed from quantum capacitance and pseudocapacitance perspectives. From the synthesized process, the TMS synthesize has been proven as good supercapacitor materials. This work gives a new perspective to process the TMS by directly grow the materials on the electrode. Moreover, this study also shows that new superstructures called as hierarchical nanopores were able to utilize TMS nanoparticle full potential. We discovered that this structure was able to optimize nanoparticle abundance surface area while maintaining structural integrity to ensure high conductivity of the electrodes. In general, this study's results also open new avenues to increase the supercapacitor performance by utilizing the nanoparticle full potential and new mechanisms such as quantum capacitance modulation